Camellia sinensis L. Extract Suppresses Inflammation on Acute Respiratory Distress Syndrome Cells Models via Decreasing IL-1ß, IL-6 and COX-2 Expressions - Widowati, Wahyu; Priyandoko, Didik; Lenny, Lenny; Revika, Revika; Novianti, Sintya; Kusuma, Hanna Sari Widya; Rizal, Rizal (Trends in Sciences, 2023)
Acute Respiratory Distress Syndrome (ARDS) is one of the clinical manifestations in severe COVID-19 patients characterized by acute inflammation resulting in respiratory failure and death. Camellia sinensis L. or green tea extract has many beneficial secondary metabolites including polyphenols which have anti-inflammatory and anti-viral roles. This study was aimed to investigate the activity of green tea extract (GTE) as an anti-inflammatory on ARDS model cells. In this study, rat lung alveolar type II epithelial cells line (L2) was induced by lipopolysaccharide (LPS) to mimic the inflammation process in ARDS. These cells were then treated with GTE to determine the GTE effectiveness in reducing the inflammation. The GTE polyphenol constitutions were first confirmed using Liquid Chromatography with Tandem Mass Spectrometry (LC-MS/MS). The cytotoxic assay was conducted using MTS assay kit to determine the safe range of GTE concentrations that used in the next assay. The effectiveness of the GTE was determined by measuring pro-inflammatory cytokines (IL-1ß and IL-6) and inflammation-mediated enzymes (COX-2), both of which were by ELISA method. Furthermore, this study measured the ACE-2 and TMPRSS-2 gene expressions by qRT-PCR method. The results showed that GTE treatment significantly reduced pro-inflammatory cytokines IL-1ß, IL-6, inflammation-mediated enzyme COX-2, and significantly increased ACE-2 and TMPRSS-2 mRNA expressions. In short, green tea extract possesses the potential to alleviate inflammation. HIGHLIGHTS Acute Respiratory Distress Syndrome (ARDS) is one of clinical manifestations in severe COVID-19 patients characterized by acute inflammation results in respiratory failure and death In lung inflammation, the Angiotensin Converting Enzyme-2 (ACE-2) and Trans-Membrane Protease Serine-2 (TMPRSS-2) genes were lowly expressed, then causes alveolar tissue collapse High levels of inflammatory mediator cytokines would be secreted in respiratory tracts, such as Interleukin (IL)-1β, IL-6, and Cyclooxygenases (COX)-2 Polyphenols in green tea (Camelia sinensis L.) have been reported to have anti-inflammatory activities GRAPHICAL ABSTRACT